Potassium, Zinc, and Boron Nutrients Effect on Sorghum (Sorghum bicolor L. Moench) Yield in Wag-Lasta, Northern, Ethiopia - Esubalew, Tilahun; Sebnie, Workat (International Journal on Food, Agriculture and Natural Resources, 2024)
In Ethiopia using inorganic fertilizer started in the early 1970s. But it still depended solely on urea and DAP. Today, according to ATA and Ministry of Agriculture and Natural Resources K, Zn, B, S, and Cu are in deficit in Ethiopia and Amhara Region as well as in Wag-Lasta areas. But some studies conducted in Wag-Lasta and throughout the region in different crops indicate that these nutrients had no response on crop yields. So, this experiment was conducted in 2017 rain feed cropping season on five farmers’ parcels per location to verify the response of sorghum to potassium, zinc, and boron nutrients. The treatments were: NPS, NPSK, NPSZnB, and NPSZnBK, with the recommended rate of 46 and 23 kg ha-1 N and P2O5,respectivelyfor Sekota,23 kg ha-1N, andP2O5 for Lasta. Moreover, 150, 1.47, and 0.07 kg ha-1 KCl, Zn, and B, respectively used uniformly in both locations. The experiment was laid out in randomized complete block design (RCBD) with three replications. The collected data were analyzed by SAS software version 9.0. Analysis of variance revealed that the application of potassium, zinc, and boron had no significant effect (P ≤0.05) on sorghum yield and yield components at all sites. The exchangeable potassium content in the soil of the study sites is above the critical value level. The result disagrees with the soil fertility map which showed more than 98% of potassium deficiency and more than 80% NPSZnB deficiency. Hence, the application of K, Zn, and B nutrients had no yield advantage over the recommended N and P nutrients in the Wag-Lasta areas. Therefore, currently to increase production and productivity of crops in Wag-Lasta areas using of recommended rate of nitrogen and phosphorous with organic fertilizer sources for each district is the best option rather than using K, Zn, and B nutrients.